MBCL-41. TREATMENT FAILURE PATTERNS ACROSS MEDULLOBLASTOMA SUBGROUPS WITHIN A PROSPECTIVE PHASE II CLINICAL TRIAL OF RISK-ADAPTED, VOLUME-REDUCED RADIATION THERAPY AND DOSE-INTENSE CHEMOTHERAPY WITH STEM CELL SUPPORT. Issue 2 (22nd June 2018) - Tinkle, Christopher; Lucas, John; Srinivasan, Sudharsan; Tumlin, Parker; Onar-Thomas, Arzu; Huang, Jie; Patay, Zoltan; Ellison, David; Orr, Brent; Northcott, Paul; Robinson, Giles; Gajjar, Amar; et al.
Abstract: PURPOSE: To characterize the patterns of progression across medulloblastoma (MB) clinical risk and molecular subgroups. METHODS AND MATERIALS: 155 pediatric patients with newly diagnosed MB were treated at our institution on a prospective, multi-center phase II trial of adjuvant RT and dose-intense chemotherapy with autologous stem cell transplant. RT included CSI to 23.4 Gy (average risk, AR) or 36-39.6 Gy (high risk, HR) followed by conformal primary site RT with a 1 cm clinical target volume to a cumulative dose of 55.8 Gy. MB subgroup was determined using 450K DNA methylation. Progression was classified by anatomic site (primary site failure (PSF) +/- distant failure (DF), or isolated DF), and RT dosimetry. RESULTS: 32 patients have progressed (median follow-up 9.0 years (range, 0.3 - 14.2 y)). Anatomic failure pattern differed by clinical risk (P=0.0054) and methylation subgroup (P=0.0001). 10-year cumulative incidence (CI) of PSF was 6.2% and 5.6% in AR and HR patients, respectively (P=0.92), and did not differ across subgroups (P=0.16). 10-year CI of DF was 8.2% vs. 28.1% for AR vs. HR (P=0.0007); and 0% for WNT, 18.4% for SHH, 39.5% for G3, and 6.4% for G4 (P<0.0001). Of 9 patients with PSF, 8 were within the primary site RT field and 4 represented SHH tumors. CONCLUSIONS: The low incidence of PSF between clinical risk groups following conformal primary site RT is comparable to prior studies using larger primary site or posterior fossa boost volumes. Distinct anatomic failure patterns across MB subgroups suggest subgroup-specific treatment strategies should be considered.